Keragaan Hasil dan Daya Toleransi Genotipe Kedelai di Lahan Sulfat Masam - Koesrini, ,; William, Eddy (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
High soil acidity is one of the problems caused low soybean productivity on acid sulphate soil. Using tolerant variety is one effort for increasing soybean productivity on acid sulphates oil. The objective of these researches were to understand the performance yield and tolerancy of soybean genotypes to acid sulphate soil. These researches were conducted on acid sulphate soil at Pindahan Baru. Jajangkit Timur and Talaran-Barito Kuala District of South Kalimantan in wet season of  2003/04. These researches were arranged in Randomized Completely Design with three replications. Five genotypes and 4 varieties were evaluated for their tolerance and yield potential. The result showed that none of the genotypes have yield higher than that of check varieties Lawit, Menyapa and Sibayak. There was one of genotypes i.e. Msc 9234-D-3 give higher yield than check varieties Tanggamus, good seed quality and tolerant to acid sulphate soil.   Key words: Performance, Soybean, Acid sulphates oil